Knowledge on Health Protocols and Anxiety of Midwives in Delivery Assistance During the Covid-19 Pandemic - Dwi Ertiana; Vesti Anggreani (EMBRIO: Jurnal Kebidanan, 2023)
In 2021, 6 out of 45 midwives at the PMC Hospital of Jombang were exposed to COVID-19. This study aims to identify the correlation between knowledge on health protocols and anxiety in delivery assistance during the Covid-19 pandemic. This was an analytical-correlational study with cross sectional approach. The independent variable was the knowledge on health protocols and the dependent variable was the level of anxiety in delivery assistance during the Covid-19 pandemic. The study was conducted at PMC Hospital of Jombang on June 28, 2021 – July 12, 2021. The study population involved all midwives at PMC Hospital of Jombang as many as 45 respondents, with a sample size of 32 respondents, who were selected using a simple random sampling technique. Data collection tool used a questionnaire. Data were analyzed using the Chi Square test. The study findings showed that 68.8 percent of respondents had a good level of knowledge on health protocols. On the other hand, 87.6 percent of respondents had mild level of anxiety in delivery assistance during the mild COVID-19 pandemic. There was a correlation between the level of knowledge on health protocols and anxiety of midwives in delivery assistance during the Covid-19 pandemic. It was obtained a p-value of (0.000) less than α equals (0.05), r equals 0.596 which indicated moderate correlation level. The higher the level of knowledge, the lower the level of anxiety. Midwives are surely able to overcome anxiety they experience through good knowledge which can encourage good spirits, especially while providing obstetric support services to patients during the Covid-19 pandemic.